2012
DOI: 10.1091/mbc.e12-02-0134
|View full text |Cite
|
Sign up to set email alerts
|

The centriolar satellite proteins Cep72 and Cep290 interact and are required for recruitment of BBS proteins to the cilium

Abstract: The ciliopathy-associated proteins Cep290 and BBS4 localize to cytoplasmic particles called centriolar satellites, yet the significance of this association is unknown. A new component of satellites, Cep72, is identified. Its role in the regulation of Cep290 and BBS4 is described, as are developmental defects resulting from loss of satellites in zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
180
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(214 citation statements)
references
References 59 publications
31
180
3
Order By: Relevance
“…Proteins that, putatively, interacted with Ccdc13 with the greatest peptide coverage were PCM1, pericentrin, Cep290, Cep215, Cep131, Cep90 and Cep72 (Fig. 3A), which have all been previously shown to localise to centriolar satellites (Balczon et al, 1994;Dammermann and Merdes, 2002;Kim et al, 2008;Kim et al, 2012;Lee and Rhee, 2010;Lopes et al, 2011;Ma and Jarman, 2011;Stowe et al, 2012). Additionally, we confirmed that YFP-Ccdc13 colocalised with PCM1 and pericentrin (Fig.…”
Section: Ccdc13 Is a Novel Human Centriolar Satellite Proteinsupporting
confidence: 81%
See 1 more Smart Citation
“…Proteins that, putatively, interacted with Ccdc13 with the greatest peptide coverage were PCM1, pericentrin, Cep290, Cep215, Cep131, Cep90 and Cep72 (Fig. 3A), which have all been previously shown to localise to centriolar satellites (Balczon et al, 1994;Dammermann and Merdes, 2002;Kim et al, 2008;Kim et al, 2012;Lee and Rhee, 2010;Lopes et al, 2011;Ma and Jarman, 2011;Stowe et al, 2012). Additionally, we confirmed that YFP-Ccdc13 colocalised with PCM1 and pericentrin (Fig.…”
Section: Ccdc13 Is a Novel Human Centriolar Satellite Proteinsupporting
confidence: 81%
“…A number of centriolar satellite proteins, such as PCM1 and the ciliopathy proteins Cep290 and Bardet-Biedl syndrome protein 4 (BBS4) cooperate in the formation of the primary cilia (Kim et al, 2008;Lopes et al, 2011;Stowe et al, 2012), an organelle that has only recently been appreciated as a crucial signalling hub for a number of pathways, which include Wnt and sonic hedgehog (Logan et al, 2011). Recent work has demonstrated that a number of proteins involved in the DNA damage response (DDR) also function during ciliogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Centriolar satellites have been implicated in centrosomal protein transport and ciliogenesis [118]. In addition to providing a platform for pro-ciliogenesis proteins, satellites suppress untimely cilia formation by sequestering key ciliogenesis factors [115,[119][120][121][122]. Thus, certain ciliopathy phenotypes could arise from ill-timed ciliogenesis and signalling.…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%
“…First, evidence suggests that hypomorphic mutations target specific aspects of protein function [126]. Second, CEP290 and OFD1 participate in multiple protein complexes during ciliogenesis, which could be differentially affected by mutations [122,123,126,143]. Last, patients often carry mutations in multiple ciliary genes [116].…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%
“…Immunostaining, using ARL13B and gamma-tubulin antibodies, revealed significantly longer cilia in Cdk10KO MEFs than in WT cells ( Figures 3F and 3G), corroborating results that were reported after the silencing of Cdk10 or cyclin M by siRNA 10 (for a review, see Guen et al 33 ). BBS4, which interacts with CEP290, 34 is a BBSome component that is essential for cilia formation, 35 providing a rationale for our observation of longer cilia in Cdk10KO MEFs.…”
Section: Mice With Mutant Cdk10 Display Defects In Multiple Organsmentioning
confidence: 75%